Price Effectiveness and Product Quality on Purchase Decisions by Printing Companies - Tri Angreni; Georgius Listen; Adrian Hidayat (eCo-Fin, 2022)
The purpose of writing this thesis is to determine the effect of screen-printing paint quality and printing prices on consumer purchasing decisions by printing companies. The study was conducted on 60 respondents through the distribution of questionnaires. The method used in this research is descriptive method and qualitative method. Based on the answers to the questionnaire, raw data has been obtained which is then processed using SPSS version 23 so that it becomes useful data for this research. In addition to calculating the relationship between the independent variable and the dependent variable, this study also calculated the relationship between variables. The correlation of the effect of paint quality on purchasing decisions is 0.721 the correlation of the effect of price on purchasing decisions is 0.529 and so it can be said that the relationship between the three variables is quite strong, thus Ho is rejected, and Ha is accepted. In the t-test, the results of t-count paint quality are 7.143, t-count prices are 6.896 and t-count when compared with t-table of 2.001 then there is a significant relationship is significant between paint quality and price on purchasing decisions by Printing Companies.